Congenital Colorectal Conditions: Caregiver Perspectives of Their Experience in the Neonatal Intensive Care Unit - Melkonian, Vatche; Bischoff, Andrea; Torre, Luis De La; Ketzer, Jill; Matkins, Kristina; Judd-Glossy, Laura (American Journal of Perinatology, 2024)
This study aimed to examine the experiences of children with colorectal conditions who spent time in the neonatal intensive care unit (NICU) and their caregivers.In March 2024, a 36-question survey was sent to the Colorectal Support Network Facebook community, to gather information from caregivers of children who have a congenital colorectal diagnosis and spent time in the NICU.Fifty-two families completed the survey. Most patients were diagnosed after birth (89.47%). Approximately half of respondents stayed in the NICU for 1 to 2 weeks (50.88%), lived less than 60 minutes away from the hospital (54.91%), and felt somewhat uncomfortable (28.07%) or very uncomfortable (21.05%) caring for their child's medical needs after discharge. Also, 49.12% of caregivers were informed of their child's future bowel control prognosis. When asked for suggestions to improve care in the NICU, common themes included the importance of having colorectal congenital anomalies addressed by colorectal surgeons and the need for families to be informed about support groups.Counseling families in the NICU with congenital colorectal conditions can be improved by providing additional information and support for families prior to discharge, informing them about their child's prognosis for bowel control and connecting them with other families.
Keywords: NICU; anorectal malformation; Hirschsprung; support group; family